2021
DOI: 10.3389/fimmu.2021.639975
|View full text |Cite
|
Sign up to set email alerts
|

The Imbalance of Circulating Follicular T Helper Cell Subsets in Primary Sjögren’s Syndrome Associates With Serological Alterations and Abnormal B-Cell Distribution

Abstract: Since B-cell hyperactivity and pathologic antibody response are key features in the immunopathogenesis of primary Sjögren’s syndrome (pSS), the role of follicular T helper (TFH) cells as efficient helpers in the survival and differentiation of B cells has emerged. Our aim was to investigate whether a change in the balance of circulating (c)TFH subsets and follicular regulatory T (TFR) cells could affect the distribution of B cells in pSS. Peripheral blood of 38 pSS patients and 27 healthy controls was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…In 2021, Szabó et al [ 32 ] published an article whose aim was to investigate whether the distribution of B cells in pSS could be affected by a change in the balance of circulating T follicular helper (Tfh) cell subsets and follicular regulatory T cells. Utilising multicolour flow cytometry, they discovered that pSS patients had a significant increase in activated Tfh cells compared to HCs.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Szabó et al [ 32 ] published an article whose aim was to investigate whether the distribution of B cells in pSS could be affected by a change in the balance of circulating T follicular helper (Tfh) cell subsets and follicular regulatory T cells. Utilising multicolour flow cytometry, they discovered that pSS patients had a significant increase in activated Tfh cells compared to HCs.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42] Similar reductions in the memory B cell compartments have been described in sarcoidosis, systemic sclerosis and Sjogren's syndrome. 40,[43][44][45][46][47][48] Comparing immunophenotype results between different studies is complex due to the variety of staining and gating protocols used, and clinical and demographic characteristics of the patient cohort, but some general conclusions can be made regarding iTTP in comparison to other autoimmune diseases. We found an increased ratio of naïve to switched memory B cells and higher plasmablasts in the acute patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are many subtypes of Tfh cells, such as Tfh1, Tfh2, and Tfh17-like cells, the latter are significantly increased in the peripheral blood of patients with SS ( 22 ). Additionally, some experiments showed that CXCR5 + PD-1 + Tfh cells in the blood of patients with SS were unchanged compared with those in individuals without SS, but the effects of Tfh1-like cells were more significant than those of Tfh2 and Tfh17-like cells ( 19 , 20 ). An increase in Tfh (CD4 + CXCR5 + ) cells was detected in the labial glands of patients with SS compared to that in normal controls.…”
Section: Role Of Cd4 + T Cells In Ssmentioning
confidence: 99%